Simulation of the dynamic response of an urban utility tunnel under a natural gas explosion. (February 2021) - Xue, Yongzhi; Chen, Guohua; Zhang, Qiang; Xie, Mulin; Ma, Jiajun
Graphical abstract: Highlights: This work studies the dynamic response of a tunnel under a natural gas explosion. Numerical models based on the coupled ALE-FEM algorithm are presented. The established models consider the dynamic properties of the gas and structure. The mechanical behaviours of the tunnel are clarified based on a simulation. The impacts of gas leakage and cube size on the results are investigated. Abstract: Based on the coupling of the arbitrary-Lagrangian-Eulerian (ALE) and finite element (FE) algorithms, the paper presents a numerical model that takes into account the fluid properties of an explosive gas and the mechanical characteristics of a structure to simulate the dynamic process of a natural gas explosion in an urban utility tunnel. The dynamic response of the tunnel is clarified by analysing the pressure, displacement, velocity, and effective stress of the structure. Furthermore, the mechanical behaviour of the tunnel in which the explosion occurs, corresponding to different gas leakages and cube sizes, is investigated. It is determined that an increase in gas leakage and decrease in cube size increase the blast pressure, propagation velocity of the explosion cloud, and effective stress acting on the tunnel.